The Effect Of Profitability, Leverage, Audit Opinions, And Company Size On The Timeliness Of Financial Reporting. - iskandar, Delis Noviawati; wafa, Zaenal (East Asian Journal of Multidisciplinary Research, 2024)
The reason of this inquire about is to decide whether the taking after factors—profitability, use, review supposition, and commerce size—have an effect on how rapidly property and genuine domain segment companies recorded on the Indonesia Stock Trade (IDX) yield their money related reports between 2020 and 2022. With a add up to test measure of 150, the ponder approach utilizes quantitative clear information that is assessed utilizing calculated relapse. The factors benefit, use, and review supposition was appeared to has a halfway effect on the opportune accommodation of monetary explanations, in any case the estimate of the company was found to have no halfway influence on the same. The components of productivity, use, review conclusion, and firm estimate all have an effect on the opportune generation of monetary explanations at the same time.